Nonvolatile tri-state resistive memory behavior of a stable pyrene-fused N-heteroacene with ten linearly-annulated rings - Li, Yang (2020)
The diverse functionalities of large N-heteroacenes continue to be developed in terms of their strategic synthesis and application in the organic electronic field. Here, we report a novel large stable pyrene-containing N-heteroacene with ten linearly-annulated rings in one row. Remarkably, it exhibited excellent tri-state resistive memory property, which held great promise to achieve ultrahigh-density data storage. To the best of our knowledge, it is the first demonstration of organic multistate memory device based on large N-heteroacene (n≥10), which provides guidelines for designing more proof-of-concept larger N-heteroacene-based memory electronics.